Solid State Properties From Bulk to Nano - Dresselhaus, Mildred (Graduate Texts in Physics,, 2018)
This book fills a gap between many of the basic solid state physics and materials science books that are currently available. It is written for a mixed audience of electrical engineering and applied physics students who have some knowledge of elementary undergraduate quantum mechanics and statistical mechanics. This book, based on a successful course taught at MIT, is divided pedagogically into three parts: (I) Electronic Structure, (II) Transport Properties, and (III) Optical Properties. Each topic is explained in the context of bulk materials and then extended to low-dimensional materials where applicable. Problem sets review the content of each chapter to help students to understand the material described in each of the chapters more deeply and to prepare them to master the next chapters.